2017
DOI: 10.1177/0046958017696757
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Expenditures Associated With Hospital and Emergency Department Use Among Beneficiaries With Dementia

Abstract: Understanding expenditure patterns for hospital and emergency department (ED) use among individuals with dementia is crucial to controlling Medicare spending. We analyzed Health and Retirement Study data and Medicare claims, stratified by beneficiaries’ residence and proximity to death, to estimate Medicare expenditures for all-cause and potentially avoidable hospitalizations and ED visits. Analysis was limited to the Medicare fee-for-service population age 65 and older. Compared with people without dementia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 36 publications
(64 reference statements)
2
29
2
Order By: Relevance
“…Contrary to our expectations and similar to other previous studies (21,64), the argument of rising medical costs resulting from living in NH was not confirmed in the RTPC sample. It was observed that medical costs associated with hospital admission (including EDA) were lower in the NH setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our expectations and similar to other previous studies (21,64), the argument of rising medical costs resulting from living in NH was not confirmed in the RTPC sample. It was observed that medical costs associated with hospital admission (including EDA) were lower in the NH setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our results, Coots Daras et al (2017) found that people with dementia in their last year of life living in NH had lower costs derived of EDA and HA than people with dementia living in the community. However, these results were not seen among the general population with dementia, for whom the costs of EDA and HA were higher among those living in NH (16). The authors discuss that expenditures associated with hospital and ED use may vary by residential setting, and proximity to death.…”
Section: Insert Table 6 Discussionmentioning
confidence: 79%
“…These conditions may increase the cost of medical care for patients with dementia. The annual mean costs of emergency department Medicare expenditures among patients with dementia were higher than those among patients without dementia (Daras et al, 2017).…”
Section: Introductionmentioning
confidence: 81%